Getting lost to find insights - a quasi-experimental evaluation of outdoor experiential learning as a method to teach clinical decision-making and decision science concepts - Sarah Petelinsek; Peilu Zhang; Jorie Colbert-Getz; Theodore Hartridge; Nate Furman; Emad Awad; Rowan Kelner; Patrick G Hughes (BMC Medical Education)
Abstract Background There is a high prevalence of errors related to decision-making biases that results in medical errors. Despite this, there is limited teaching on decision-making biases in medical education. Study hypothesis or objective This study aimed to evaluate outdoor experiential learning as a mechanism to teach decision-making to first year medical students. Methods As a quasi-experimental study, the first year medical students at our institution were invited to participate in a brief workshop that included an introductory discussion followed by a guided hiking experience. During the hike, the guides were instructed to intentionally lead students off the outlined path and into a commonly experienced decision-making error, authoritative bias. This provided the students with a first-hand experience of the consequences of decision-making biases. Student experience was evaluated with a pre and post course test designed to evaluate participants’ knowledge on the decision-making biases, and decision science concepts that were covered both in the experiential, and didactic portions of the workshop. Results Of the 120 students who participated in the workshop, 41 students completed the pre course and post course evaluation. The overall pre-quiz scores, and post-quiz scores were evaluated. Results of a paired sample t-test indicated a statistically significant improvement in scores [t(40) = 7.64, p < 0 0.001]. The Mean Pre-Quiz Score was 51.83% ± 18.40, the Mean Post-Quiz Score was 74.09 ± 18.40. This represents a 22.26% (95% CI: 16.37–28.14) score increase from pre-quiz to post-quiz (p < 0.001). Conclusions The results suggest that this novel outdoor experiential learning workshop was an effective method of introducing decision-making biases and general decision science concepts to first year medical students. Future iterations of this work can investigate long-term retention of these concepts, comparison of this method to a traditional classroom method, and changes in clinical practice and decision-making behavior following completion of the course. Clinical trial number Not applicable.